Efeito dos fungicidas mancozeb, captan e dithianon sobre Saccharomyces cerevisiae - Scariot, Fernando Joel (My University, 2017)
Fungicides are currently used to control fungal phytopathogenic diseases in many crops, including fruits. These compounds, especially those described as multisite activity fungicides, can affect non-target organisms like yeasts leading to their cell death by different pathways. The objective of this work was determining the mechanism of action and death of three fungicides used in viticulture (captan, dithianon and mancozeb) on Saccharomyces cerevisiae. The results showed that yeast exposition to the mancozeb (100 µM, 6 h) lead to a drastic reduction of cell viability, but no modification of cell membrane integrity. Mancozeb treated cells shown apoptotic markers as increase of intracellular reactive oxygen species (ROS), mitochondrial membrane hyperpolarization, and phosphatidylserine externalization, indicating that mancozeb induced cell death in S. cerevisiae is apoptotic and as shown by mutants strains, follow metacaspase-dependent pathway. Almost 80% of captan treated yeasts (20 µM, 6 h) showed citoplasmatic membrane dysfunction, and a drastic reduction on both non-proteic and proteic thiol concentrations. Moreover, the cells that retain their membrane integrity after exposure to the captan exhibited phosphatidylserine externalization and ROS accumulation, indicating apoptosis. YCA1 deletion mutant exhibited partial resistance to captan, suggesting a metacaspase dependent apoptotic cascade. In wine fermentations captan (2,5 µM) delays the beginning of alcoholic fermentations in a dose dependent manner, associated with a drastic reduction on yeast viability. However, in sub-lethal dosages, the reminiscent viable cells adapted to the fungicide, grow and complete fermentation with non-evident modifications on the physicochemical characteristics of the final product. Similarly, yeast cells treated with dithianon (2 µM; 3 h) showed cell membrane permeabilization, ROS increase, and decrease of cellular thiol compounds, but no signs of apoptosis. In general, the results indicated that mancozeb induces metacaspase dependent apoptotic cell death in S. cerevisiae, where captan leads to a dual necrotic and apoptotic cell death, and dithianon kills cells by necrosis.
Os fungicidas são normalmente utilizados para o controle de doenças causadas por fungos fitopatogênicos em diversas culturas, incluindo frutas. Estes compostos, especialmente os descritos com atividade em múltiplos alvos, podem afetar organismos não alvos como leveduras, levando elas à morte por diferentes vias. O objetivo deste trabalho foi determinar o mecanismo de ação e de morte de três diferentes fungicidas utilizados na viticultura (mancozeb, captan e dithianon) sobre Saccharomyces cerevisiae. Os resultados mostraram que leveduras expostas ao mancozeb (100 µM, 6 h) levam a uma drástica redução da viabilidade, mas sem modificações na integridade da membrana celular. As células tratadas com mancozeb apresentaram marcadores apoptóticos como aumento na concentração intracelular de espécies reativas de oxigênio (ROS), hiperpolarização da membrana mitocondrial e externalização de fosfatidilserina, indicando que a morte celular de S. cerevisiae ocasionada por mancozeb é apoptótica e conforme observado pelo comportamento de linhagens mutantes, segue a via metacaspase dependente. Aproximadamente 80% das leveduras tratadas com captan (20 µM, 6 h) apresentaram disfunções na membrana citoplasmática, e a drástica redução na concentração de grupos tiólicos proteicos e não proteicos. Além disso, as células que mantiveram sua integridade de membrana após a exposição ao captan, exibiram externalização de fosfatidilserina e acumulação de ROS. Mutantes com deleção em YCA1 apresentaram resistência parcial ao captan, indicando a ativação da cascata apoptótica metacaspase dependente. Em fermentações vínicas o captan (2,5 µM) atrasa o início da fermentação de maneira dose dependente, devido à drástica redução na viabilidade celular. Porém, em dosagens subletais, as células remanescentes se adaptam ao fungicida e completam a fermentação sem alterações evidentes nas características físico-químicas do produto final. Da mesma forma, leveduras tratadas com dithianon (2 µM; 3 h) mostraram aumento no número de células com permeabilização da membrana citoplasmática, aumento de ROS e redução na quantidade de tióis, mas sem sinais de apoptose. De forma geral, os resultados indicam que o mancozeb induz apoptose em S. cerevisiae via metacaspase dependente, enquanto o captan leva a morte por necrose e apoptose e o dithianon mata as células por necrose.
Keywords: Fungicidas; Uvas - Cultivo; Fungicides; Viticulture